INTERNALISASI NILAI-NILAI SPIRITUAL UNTUK PEMBENTUKAN KARAKTER SISWA SD ISLAM KURMA SALATIGA - Nafingatun; Muh Nursikin (STKIP Subang, 2026)
This study aims to examine in depth the mechanisms and strategies for internalizing spiritual values at SD Islam Kurma Salatiga in shaping student integrity, with a primary focus on exploring a holistic strategy that bridges ritualistic practices into transformative behavior. Employing a qualitative method with a case study design, data were collected through in-depth interviews, participant observation, and documentary studies, which were then analyzed using the interactive model of Miles, Huberman, and Saldana through the lenses of Herbert Kelman’s internalization theory and Al-Attas’s concept of ta’dib. The results indicate that the internalization of spiritual values is carried out through three simultaneous stages: first, the institutionalization of values through an integrated curriculum (hablum minallah, minannas, minal ‘alam), habituation, and teacher exemplary behavior (uswah hasanah); second, the subjectification of values through the pedagogical technique of the